Athens and Macedon : Attic letter-cutters of 300 to 229 B.C - Tracy, Stephen V. (Hellenistic culture and society, 2003)
Cover; Contents; Figures; Abbreviations; Preface; Introduction; PART I: ATHENIAN GOVERNMENT AND THE MACEDONIAN KINGS; PART II: ATTIC LETTER-CUTTERS OF 300 TO 229 B.C.; Appendix One: Athenian Archons from 261/0 to 234/3; Appendix Two: Agora I 5392 + 3855: A Prytany Decree from ca. 275-270 B.C.; Index to Greek Texts; Index of Passages Cited; Index of Persons; General Index; Comparatio Numerorum; Comparatio Numerorum to SEG.